Analysis of permeability of gypsum-treated basaltic sand and study of makeshift permeameter prototypes - De Grano, Princess Maica A.; Lemos, Darryl O.
Basaltic sand is commonly used as a material in construction, while gypsum powder is used as coating for finish in buildings. In this study, the permeability of basaltic sand treated with gypsum powder in varying amounts is analyzed to assess its suitability as a fill material for impervious structures such as embankments. Moreover, designs of makeshift permeameter prototypes are studied to produce an instrument that will lessen the constraint in conducting permeability experiments. Falling head test was used in evaluating the permeability of the gypsum-treated basaltic sand. The results range from 4x 10^-4 to 8x10^-4 cm/s. Based from the order of the values (x1O^-4 cm/s), the gypsum does not significantly affect the permeability of the basaltic sand. On the other hand, the makeshift permeameter was made from readily available materials such as 4" polyvinylchloride (PVC) pipe for the casing, vinyl tubing for the influent line, scrub as porous stone alternative, and filter paper and wire mesh for the bottom filter. Using the same testing methodology, permeability values were also determined using the makeshift permeameter. These values were compared with the values obtained from an actual permeameter to assess its accuracy.